2022
DOI: 10.1038/s41598-022-18618-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of influenza vaccine in reducing the severity of clinical outcomes in patients with COVID-19: a systematic review and meta-analysis

Abstract: Recent evidence suggests that vaccination against influenza may reduce the clinical outcomes of COVID-19. This study looked at the link between influenza vaccination and the severity of COVID-19 infection. We searched five databases until August 2021. We included studies that reported the relationship between influenza vaccination and COVID-19 outcomes. We pooled the data as risk ratio (RR) or mean difference (MD), with 95% confidence intervals (CIs), the data pooled using fixed and random effects models accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(118 reference statements)
2
9
0
Order By: Relevance
“…A meta-analysis study revealed a significant advantage for mechanical ventilation in COVID-19 individuals who had received an influenza vaccination over those who had not. 33 Another meta-analysis of observational studies included 290,327 participants claimed that receiving an influenza vaccination decreases the chance of COVID-19 infection which is in agreement with the findings of our study. 34 On the other hand, the relationship between the influenza vaccine and a decreased risk of COVID-19 negative outcomes was discussed by Fink et al 35 This included the ability of live vaccines to activate trained innate immunity and produce known "off-target" protection against infections other than those specifically targeted by the vaccine.…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis study revealed a significant advantage for mechanical ventilation in COVID-19 individuals who had received an influenza vaccination over those who had not. 33 Another meta-analysis of observational studies included 290,327 participants claimed that receiving an influenza vaccination decreases the chance of COVID-19 infection which is in agreement with the findings of our study. 34 On the other hand, the relationship between the influenza vaccine and a decreased risk of COVID-19 negative outcomes was discussed by Fink et al 35 This included the ability of live vaccines to activate trained innate immunity and produce known "off-target" protection against infections other than those specifically targeted by the vaccine.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, systematic reviews have identified that influenza vaccination is a cost-saving or cost-effective intervention [ 9 , 10 ]. Moreover, a recent meta-analysis [ 11 ] showed that influenza vaccination was associated with a reduced risk of mechanical ventilation among COVID-19 patients, while another meta-analysis [ 12 ] showed a lower risk of COVID-19 infection and influenza leading to hospitalization among the vaccinated group compared to the non-vaccinated group.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these findings were limited to the first wave of the pandemic and did not therefore account for a larger spectrum of disease severity. Finally, the available meta‐analyses 6,26 have reported contrasting results in terms of different COVID‐19‐related outcomes, underlying a high level of heterogeneity among the included studies. In this regard, the presence of bias due to the ‘healthy vaccinee’ effect has been demonstrated as a major source of inconsistencies among previous studies 7 …”
Section: Discussionmentioning
confidence: 99%